Determinants of death anxiety in patients with advanced cancer. Issue 4 (22nd August 2013) - Neel, Caroline; Lo, Chris; Rydall, Anne; Hales, Sarah; Rodin, Gary
Abstract : Objective: To examine the presence of death anxiety in patients with advanced cancer and to identify the psychosocial and disease-related factors associated with it. Design: Cross-sectional analysis of baseline data from a phase 2 pilot intervention trial. Setting: Princess Margaret Cancer Centre, University Health Network, Toronto, Canada. Participants: 60 adult outpatients with metastatic breast, endocrine, gastrointestinal, gynaecological, genitourinary and lung cancer. Main outcome measure: Death anxiety, as measured by the Death and Dying Distress Scale (DADDS). Results: Thirty-two per cent of the sample reported death anxiety of at least moderate severity. The most distressing concern involved fears about the impact of one's death on others, and the least distressing concerns were related to dying alone or suddenly. According to regression analyses, death anxiety was negatively associated with self-esteem, b=−1.73, CI0.95 (−2.57 to −0.90) and positively associated with physical symptom burden, b=1.38, CI0.95 (0.44 to 2.31), having children under 18 years of age in the family, b=13.3, CI0.95 (2.15 to 24.5), and age, b=0.40, CI0.95 (0.0023 to 0.79). The physical symptoms most strongly associated with death anxiety were changes in physical appearance, b=18.8, CI0.95 (8.21 to29.5), and pain, b=10.1, CI0.95 (0.73 to 19.5). Conclusions: The findings suggest that death anxiety in patients with advanced cancer is common and determined by the interaction of individual factors, family circumstances and physical suffering. Multidimensional interventions that take into account these and other factors may be most likely to be effective to alleviate this death-related distress.